Internalisasi Nilai Pendidikan Sosial (Al-Tarbiyah Al-Ijtima’iyyah) Al-Quran dalam Membentuk Kesadaran Kolektif Masyarakat Berkeadaban: INTERNALISASI NILAI PENDIDIKAN SOSIAL (Al-TARBIYAH Al-IJTIMAIYYAH) AL-QURAN DALAM MEMBENTUK KESADARAN KOLEKTIF MASYARAKAT BERKEADABAN - ABDURRAHMAN, FATMA AMALIA RAHMA; Abd. Basir; Ali Mu’ammar Zainal Abidin (Institut Agama Islam Darul Ulum Kandangan, 2025)
Social education, or al-tarbiyah al-ijtima'iyyah in Islam, is a vital dimension that combines individual piety with social responsibility. This study aims to explore the values ​​of social education in the Qur'an and the influence of their internalization on the formation of collective consciousness toward a civil society. Using qualitative methods based on literature, this study analyzes Qur'anic verses related to social interaction and justice. The findings indicate that the values ​​of ukhuwah (brotherhood), ‘adl (adl), deliberation (musyawarah), and ta'awun (conciliation) are the main pillars of social education. Strengthening these values ​​through an integrative curriculum and social project-based learning is a crucial strategy for producing a generation with empathy and moral integrity in the contemporary era. Keywords: Al-Tarbiyah Al-Ijtima'iyyah, Al-Quran, Collective Consciousness, Civilized Society